2019
DOI: 10.1128/mbio.01726-18
|View full text |Cite
|
Sign up to set email alerts
|

Rad53- and Chk1-Dependent DNA Damage Response Pathways Cooperatively Promote Fungal Pathogenesis and Modulate Antifungal Drug Susceptibility

Abstract: Genome instability is detrimental for living things because it induces genetic disorder diseases and transfers incorrect genome information to descendants. Therefore, living organisms have evolutionarily conserved signaling networks to sense and repair DNA damage. However, how the DNA damage response pathway is regulated for maintaining the genome integrity of fungal pathogens and how this contributes to their pathogenicity remain elusive. In this study, we investigated the DNA damage response pathway in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 74 publications
(93 reference statements)
2
34
0
Order By: Relevance
“…Therefore, we questioned whether TOR1 overexpression might influence Rad53 activity. As previously reported (Jung et al 2019), Rad53 was quickly phosphorylated in response to MMS in the WT strain ( Figure 4C; left panel). However, MMS-mediated Rad53 phosphorylation did not occur in the TOR1oe strain ( Figure 4C; middle panel).…”
Section: Tor1 Negatively Regulates the Thermotolerance Of C Neoformanssupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, we questioned whether TOR1 overexpression might influence Rad53 activity. As previously reported (Jung et al 2019), Rad53 was quickly phosphorylated in response to MMS in the WT strain ( Figure 4C; left panel). However, MMS-mediated Rad53 phosphorylation did not occur in the TOR1oe strain ( Figure 4C; middle panel).…”
Section: Tor1 Negatively Regulates the Thermotolerance Of C Neoformanssupporting
confidence: 86%
“…It has been recently demonstrated that Rad53 is the central protein kinase in the regulation of genes involved in DNA damage repair in C. neoformans (Jung et al 2019). Therefore, we questioned whether TOR1 overexpression might influence Rad53 activity.…”
Section: Tor1 Negatively Regulates the Thermotolerance Of C Neoformansmentioning
confidence: 95%
See 2 more Smart Citations
“…Activation of the ATR-CHK1 pathway can cause cell cycle arrest to allow cellular repair or induce cell death when the damage is irreparable. [28]In our study, the PARP inhibitor olaparib induced levels of several important HR-related factors in Cal27 and Scc25 cells, indicating that HR is induced in response to olaparib. We further found that olaparib upregulates the expression of the ATR/CHK1 pathway, which may contribute to HR repair in OSCC cells.…”
Section: Discussionsupporting
confidence: 49%